MOS Current Mode Logic with Capacitive Coupling. (5th November 2012) - Gupta, Kirti; Pandey, Neeta; Gupta, Maneesha
Abstract : A new MOS current mode logic (MCML) style exhibiting capacitive coupling to enhance the switching speed of the digital circuits is proposed. The mechanism of capacitive coupling and its effect on the delay are analytically modeled. SPICE simulations to validate the accuracy of the analytical model have been carried out with TSMC 0.18  μ m CMOS technology parameters. Several logic gates such as five-stage ring oscillator, NAND, XOR2, XOR3, multiplexer, and demultiplexer based on the proposed logic style are implemented and their performance is compared with the conventional logic gates. It is found that the logic gates based on the proposed MCML style lower the delay by 23 percent. An asynchronous FIFO based on the proposed MCML style has also been implemented as an application.